Study of Wet Land of Kanwar Lake in Respect of Pollution: Assessment of Water Quality in Kanwar Lake Wetland (Journal of Advances and Scholarly Researches in Allied Education, 2011)
All life on earth relies upon water, new water is a basic, limited, powerless, inexhaustible characteristic asset on the earth and assumes as significant part in our living condition without it life is unimaginable. The current examination has been anticipated appraisal and observing of water nature of Kanwar Lake Begusaria, Bihar. Month to month variety of water nature of Kanwar Lake was examined during January to June 2017. The variety in physical and synthetic boundaries like pH, electrical conductivity, and turbidity, absolute broke up solids, alkalinity, and chloride, all out hardness, calcium hardness, organic oxygen request, broken up oxygen, substance oxygen request and iron were dissected. All boundaries aside from natural oxygen request and absolute broke up solids were found under as far as possible.